Assessment of the level of welfare under modern pig-keeping technologies, taking into account their ethological needs and characteristics - N. Yu. Krempa; O. V. Kozenko; B. V. Gutyj; I. V. Dvyliuk; N. V. Magrelo; H. V. Klym; T. V. Martyshuk; U. M. Vus; A. O. Vysotskyi (Науковий вісник Львівського національного університету ветеринарної медицини та біотехнологій імені С.З. Ґжицького: Серія Ветеринарні науки)
The issue of animal welfare has become an essential subject of discussion, leading to the need for an objective assessment of the use of technologies and systems in pig farming. The work aimed to detail the issue of ensuring animal welfare in pig farms and analyze modern pig-keeping technologies' compliance with their species. These ethological, biological, and physiological characteristics should be considered to provide and maintain an appropriate level of welfare. The analysis of intensive pork production technologies and pig-keeping systems was carried out following the “Five Freedoms” principles. Analyzing the results of studies on ensuring “freedom from hunger and thirst”, it was found that sows of all physiological periods and young animals of different age and technological groups had free access to feed and water. However, the level of balance of rations for gilts, farrowing sows, and suckling sows had certain discrepancies concerning the physiological needs of animals. Single sows were kept in stalls with an area of 2 m2 per animal, which corresponds to the design norm for keeping sows of this physiological period; however, the use of a fixed method of keeping farrowing and nursing sows, although technologically justified, nevertheless such conditions limit the animal in free movement in space, and the failure to realize instincts and needs harms the mental health of sows. This, violating the observance of “freedom from discomfort”, shortens the period of their exploitation and worsens the quality of their products. The lack of exercise throughout the pork production cycle partially deprives pigs of the freedom to manifest and implement natural behavior. The implementation of freedom from pain, injuries, or disease deserves special attention, which is carried out with a preventive purpose, conducting planned deworming, vaccinations, and vitamin therapy. Guided by the EU Directive “On minimum standards for the protection of pigs”, one should choose such options for raising these animals that would be as close as possible to natural ones and ensure the implementation of the principles of the “Five Freedoms” by the animals, with mandatory consideration of species, ethological, biological and physiological needs, and characteristics.